Die mite én die rite. Heuristiese oorwegings vir liturgiehistoriese navorsing na aanleiding van resente ontwikkelings in die liturgiewetenskap - Wepener, C (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
This article surveys developments in liturgical research in South Africa, specifically also the Reformed tradition and the discovery of the important link between liturgy and identity formation on the one hand. On the other hand developments within the field of Liturgical Studies, especially also as pertaining to the History of Liturgy is explored. It is concluded that in the light of these developments, there are a series of methodological considerations that should be taken into account by any research undertaken in the area of the history of the liturgy in South Africa which aims at implicating the connection, also in the past, between liturgy and identity formation.